Growth of cranial synchondroses and sutures requires polycystin-1 - Kolpakova-Hart, Elona (2008)
In vertebrates, coordinated embryonic and postnatal growth of the craniofacial bones and the skull base is essential during the expansion of the rostrum and the brain. Identification of molecules that regulate skull growth is important for understanding the nature of craniofacial defects and for development of non-invasive biologically based diagnostics and therapies. Here we report on spatially restricted growth defects at the skull base and in craniofacial sutures of mice deficient for polycystin-1 (Pkd1). Mutant animals reveal a premature closure of both presphenoid and sphenooccipital synchondroses at the cranial base. Furthermore, knockout mice lacking Pkd1 in neural crest cells are characterised by impaired postnatal growth at the osteogenic fronts in craniofacial sutures that are subjected to tensile forces. Our data suggest that polycystin-1 is required for proliferation of subpopulations of cranial osteochondroprogenitor cells of both mesodermal and neural crest origin during skull growth. However, the Erk1/2 signalling pathway is up-regulated in the Pkd1-deficient skeletal tissue, similarly to that previously reported for polycystic kidney.